Pelayanan perpustakaan desa berbasis inklusi sosial di Perpustakaan Desa Jendela Dunia Kabupaten Kuningan Jawa Barat - Neneng Komariah; Encang Saepudin; Evi Nursanti Rukmana (Berkala Ilmu Perpustakaan dan Informasi, 2021)
Introduction. A village library is a public library that support rural community education activities. The village library should be transformed into a sosial inclusion-based library. The paper aims to explore services and activities of Jendela Dunia Village Library based on sosial inclusion. Data Collection Method. This paper used a qualitatative research method with a case study approach. Data Analysis. The data collection techniques were conducted through interviews, observations, and library studies. Results and Discussion. The Jendela Dunia Village Library has been run based on sosial inclusion considering aspects of collection development to support the needs of the community with a web-based digital library. Several activities have also been conducted such as organising training of computer, making handicrafts, arts, and gymnastics, organisings innovative KOBOK services, managing mobile reading bicycles, and supporting health literacy through Posyandu and Posbindu. Conclusion. Jendela Dunia Village Library is a sosial inclusion-based library that is creatively managed and has the full support of the village leader. This can be a model for other village libraries in utilizing the potential of the village. Jendela Dunia Village Library also opens training sfor library managers outside the village.